Evaluation Criteria for Determining Priorities for Wildlife Conservation - Singh, H. S. (Indian Forester, 1997)
In this paper an attempt has been made to evolve It new mcthodology, tested for all Wildlife Protected Areas in Gujarat. The method prescribed is subject to modification after dcliberating various issues. Maximum weightage is alloted to biological and ecological features which decide the conservation value of the area.